2017
DOI: 10.3389/fgene.2017.00105
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Mutation of Paternal IGF2 Gene Causing Silver–Russell Syndrome in a Sporadic Patient

Abstract: Silver–Russell syndrome (SRS) is a rare, but well-recognized disease characterized by growth disorder. To date, there are two reports arguing IGF2 mutation for the onset of SRS. Herein, we present another sporadic case harboring IGF2 mutation. The male proband was the first and only child of a non-consanguineous Chinese couple. He was small for gestational age, with relative macrocephaly at birth. Severe feeding difficulties, low feeding, and growth retardation were revealed during neonatal period. At 4.5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 20 publications
1
26
0
2
Order By: Relevance
“…Additionally, no exons indel was found by checking the NGS data. We recently encountered a patient with genetic disorder caused by imprinting gene 9 , therefore, we focused on the variants of imprinted genes. Finally, we locked into a genetic variant in MAGEL2 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, no exons indel was found by checking the NGS data. We recently encountered a patient with genetic disorder caused by imprinting gene 9 , therefore, we focused on the variants of imprinted genes. Finally, we locked into a genetic variant in MAGEL2 .…”
Section: Resultsmentioning
confidence: 99%
“…3F). Next, we investigated the capacity of the p.I66S variant to activate IGF1R, whereby an empty vector and the Schematic illustration of so far identified IGF2 mutations (9,11,12). IGF2 encode an inactive 180-aa (Isoform 1, NP_000603) or 236-aa (Isoform 2, NP_001121070) precursor protein that includes a 24-aa signal peptide (SP), a 67-aa core IGF2 and a 89-aa trailer sequence (18).…”
Section: The Igf2 Mutant Prevents Igf1r Activation Probably Through Amentioning
confidence: 99%
“…Begemann et al reported the first heterozygous IGF2 variation (NM_001127598: c.191C→A, p.Ser64Ter) in a multigenerational family with a severe growth retardation (9). Habib ), which might influence IGF2/IGF1R interaction (10,12). All mutations are located on the paternal allele.…”
Section: Introductionmentioning
confidence: 99%
“…Through exome analysis, the authors identified an IGF2 nonsense mutation in all patients, inherited from their healthy fathers (OMIM 616489) (51). After this first report, other five studies identified variants in IGF2 gene on the paternal allele causing SRS-like (52)(53)(54)(55)(56). Up to now, one missense and six loss-of-function variants (3 frameshift, 2 nonsense and 1 splice-site) in the IGF2 gene were reported.…”
Section: Igf2 Defectsmentioning
confidence: 98%
“…Five probands presented cardiac abnormalities, including patent ductus arteriosus and atrial or ventricular septal defects. Male genital abnormalities, as hypospadia, penoscrotal transposition, cryptorchidism and ambiguous genitalia were also reported (51)(52)(53)56).…”
Section: Igf2 Defectsmentioning
confidence: 99%